2020
DOI: 10.1111/jfbc.13535
|View full text |Cite
|
Sign up to set email alerts
|

Coffee consumption revealed sex differences in host endogenous metabolism and gut microbiota in healthy adults

Abstract: Williamson, 2017) such as chlorogenic acids which is a major source of antioxidants, and contains significant amount of polysaccharides such galactomannans and arabinogalactan (Gniechwitz,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Coffee has been confirmed to confer various health benefits, and drinking coffee can alter a host's gut microbiota (Chong et al, 2020). Coffee may partly depend on the modulation of gut microbiota to influence health (González et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Coffee has been confirmed to confer various health benefits, and drinking coffee can alter a host's gut microbiota (Chong et al, 2020). Coffee may partly depend on the modulation of gut microbiota to influence health (González et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…These differences may confound the association between coffee drinking and health outcomes across the world. In addition, biological differences may exist between men and women in response to caffeine consumption [51,52]. There might a potential gender difference in hemodynamic effects of coffee in the body [53].…”
Section: Cups Per Day Amentioning
confidence: 99%
“…In a more recent study conducted on a small number (30) of healthy volunteers, it was found that coffee administration led to alterations in the gut microbiota, although this was not significant [56].…”
Section: Studies On Humansmentioning
confidence: 89%